Ultra-high molecular weight polyethylene polymers with improved processability and morphology

By using transition metal composites on the granular catalyst support, UHMWPE polymers with high bulk density and high intrinsic viscosity are solved, and the problems of poor processing performance and poor powder morphology of UHMWPE polymers are achieved under high stretch ratio Solid tensile and high-strength and modulus products under solvent-free conditions.

CN116057082BActive Publication Date: 2025-02-25SABIC GLOBAL TECHNOLOGIES BV
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
CN202180054087.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-03
Filing Date
2021-08-30
Publication Date
2025-02-25
Estimated Expiration
2041-08-30

AI Technical Summary

Technical Problem

The existing UHMWPE polymers have high tangle density during processing and solid-state stretching, resulting in poor processing performance and poor powder morphology, and the inability to achieve high strength and modulus at high stretching ratios.

Method used

By using transition metal composites on a granular catalyst support, UHMWPE polymers with high powder bulk density and high intrinsic viscosity can achieve a solid stretching ratio under solvent-free conditions at high stretching temperatures.

Benefits of technology

The high bulk density and high tensile ratio solid-state stretching of UHMWPE polymer are achieved, which gives excellent strength and modulus to the product, and avoids the problem of reactor scaling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004104084150000121
    Figure BDA0004104084150000121
  • Figure BDA0004104084150000131
    Figure BDA0004104084150000131
  • Figure BDA0004104084150000141
    Figure BDA0004104084150000141
Patent Text Reader

Abstract

The present invention relates to an ultra-high molecular weight polyethylene polymer having the following properties: a powder bulk density of at least 200 kg / m 3 , preferably at least 300 kg / m 3 ; The intrinsic viscosity (IV) is at least 8.0 dl / g, preferably at least 10.0 dl / g, as measured by ASTM D4020; and wherein when the stretching temperature is ≥ T m When stretched at -30°C, a sample prepared from the ultra-high molecular weight polyethylene can be stretched in the absence of a solvent at a total stretch ratio of at least 50.0, preferably at least 90.0, wherein T m is the melting temperature of the ultra-high molecular weight polyethylene polymer. The present invention also relates to a supported catalyst system for producing such UHMWPE polymer and an article obtained from such polymer having good strength and modulus.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of ultra-high molecular weight polyethylene (UHMWPE) polymers with improved processing properties and powder morphology. In particular, the present invention relates to UHMWPE polymers that can solid-state stretch polymer samples at high stretch ratios while imparting desired strength and modulus to articles. Background Art

[0002] Ultra-high molecular weight polyethylene (also known as UHMWPE) is a special class of polyolefins that have extremely high molecular weights compared to conventional polyethylene polymers. The high molecular weight characteristics of UHMWPE polymers impart excellent strength and modulus to articles produced from such polymers. However, due to this characteristic of high molecular weight, UHMWPE polymers exhibit poor flow properties, which in turn affects the processing properties of these polymers, especially when conventional processing techniques such as melt spinning or melt extrusion are applied. The root cause of the poor processing properties can be traced back to excessive polymer chain entanglements.

[0003] Conventional UHMWPE polymers have low draw ratios due to their high degree of polymer chain entanglement, which in turn adversely affects the strength and modulus of the produced articles, as described in the publication (Smith et al.) Journal of Materials Science, 1980 (15), pages 505-514. In fact, the published publication Journal of Materials Science 1987 (22), pages 523-531 describes that conventional UHMWPE polymers cannot be solid-state stretched at high draw ratios (draw ratio>10) due to polymer chain entanglement. Therefore, reducing polymer chain entanglement is considered to be a key consideration for improving the processing properties of UHMWPE polymers. In the past, the processing properties of UHMWPE polymers have been improved by applying solution spinning methods, in which the entanglement density of the polymer is reduced when the polymer is dissolved in a solvent. However, solution spinning requires a large amount of organic solvent to achieve the process, which increases the complexity of the operation, such as the circulation and recovery of the solvent and the disposal of these solvents.

[0004] Another important parameter for evaluating UHMWPE polymers is their powder bulk density, which indicates the quality of the powder form. As described in the published application WO2009112254, the bulk density of UHMWPE polymers should be high to ensure efficient processing of the polymer and to ensure efficient storage and transportation of the polymer. Therefore, both industry and academia require that UHMWPE polymers have a high bulk density and can be solid-state stretched at a high stretch ratio, while giving the desired mechanical properties such as strength (breaking strength) and modulus to the products produced from such polymers.

[0005] Disentangled UHMWPE polymer (d-UHMWPE) is a class of UHMWPE polymers that can be solid-state stretched and provide another possible solution for improving the processing properties of UHMWPE. Disentangled UHMWPE polymers are different from low-entangled UHMWPE polymers, which are reported in previous publications Macromolecules 2011, 44, 14, pp. 5558-5568 ("Macromolecules 2011"). Compared with low-entangled UHMWPE polymers, disentangled UHMWPE polymers can be solid-state stretched in a wider stretching temperature range and provide higher breaking strength at a given stretch ratio. But compared to low-entangled UHMWPE polymers, disentangled UHMWPE polymers often have an unwanted bulk density. In particular, this difference between disentangled and low entanglement UHMWPE polymers is clearly seen from the results shown in Macromolecules 2011, where the disentangled UHMWPE polymer exhibits higher strength than the low entanglement UHMWPE polymer, but inferior bulk density.

[0006] Published patent application WO87 / 03288 (Smith et al.) describes a UHMWPE polymer that can be solid-state stretched at a temperature below the melting temperature of the polymer. As described in patent WO87 / 03288, the disentangled UHMWPE polymer can be directly used to produce high-strength and high-modulus films and fibers without involving complex processing steps such as spinning, casting, dissolving and drying. However, some properties of the UHMWPE polymer described in patent WO87 / 03288 indicate that its powder morphology is poor and not suitable for industrial production. Although the invention described in WO87 / 03288 aims to improve the stretch ratio of the UHMWPE polymer, the stretch ratio confirmed in the patent can still be further increased, for example, to more than 50, thereby further improving strength and modulus. In addition, the catalyst system described in patent publication WO87 / 03288 is prone to cause reactor fouling, which will lead to unplanned shutdown of the reactor and reduced productivity.

[0007] Although other publications such as published patent applications WO2013076733, WO2013 / 118140, US2012095168 or the published article Macromolecules 2011 provide some useful ideas in developing disentangled and / or low entangled UHMWPE polymers, the polymers described in these publications still have low powder bulk density and irregular powder shape, which indicates that their powder morphology is poor. On the other hand, published patent application WO93 / 15118 describes a bulk density of up to 300 kg / m 3The invention relates to the production of ethylene polymers having a draw ratio of at least 20. However, the patent describes by way of example polymers having relatively moderate draw ratios, which, although promising, can be further improved. In addition, the polymers described in the application WO 93 / 15118 are produced using Zeigler Natta catalysts, which generally produce low entanglement UHMWPE polymers and do not impart the desired strength and modulus to the produced articles. Summary of the invention

[0008] Therefore, there remains a need to develop UHMWPE polymers having one or more of the following advantages: (i) having high bulk density, (ii) being solid state drawn at high draw ratios in the absence of solvent, and (iii) imparting desirable strength and modulus to articles made from such UHMWPE polymers. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] For a more comprehensive understanding, the following description is provided in conjunction with the accompanying drawings, in which:

[0010] Figure 1 Graphs showing the breaking strength of tapes prepared according to Examples 1-4 and stretched at different stretch ratios.

[0011] Figure 2 This is a scanning electron microscope (SEM) image of the polymer powder (sample code: 20190925AKO2) prepared according to Example 1 of the present invention.

[0012] Figure 3 This is the SEM image of the polymer powder prepared in Comparative Example 3 (sample code: 20191127AKO2).

[0013] Figure 4 It is a SEM image of the polymer powder prepared in Comparative Example 4 (sample code: ACE-170922-uh1). DETAILED DESCRIPTION

[0014] Thus, one object of the present invention includes providing an ultra high molecular weight polyethylene (UHMWPE) polymer having one or more of the following advantages: (i) having a high bulk density, (ii) being solid state stretched at high draw ratios in the absence of solvent, and (iii) imparting desirable strength and modulus to articles made from such UHMWPE polymers. Another object of the present invention is to provide a catalyst system suitable for producing a disentangled UHMWPE polymer having a desirable powder morphology, but without causing reactor fouling. Yet another object of the present invention is to prepare articles, such as tapes, fibers and filaments, having high strength and modulus.

[0015] The object of the present invention is achieved by providing an ultra-high molecular weight polyethylene polymer having the following properties:

[0016] The bulk density of the powder is at least 200 kg / m3 as measured by ASTM D1895 / A (1996, reapproved 2010-e1) 3 , preferably at least 300 kg / m 3 ;

[0017] An intrinsic viscosity (IV) of at least 8.0 dl / g, preferably at least 10.0 dl / g, as measured by ASTM D4020 (2005); and

[0018] When the stretching temperature ≥ T m When stretched at -30°C, a sample prepared from the ultra-high molecular weight polyethylene can be stretched in the absence of a solvent at a total stretch ratio of at least 50.0, preferably at least 90.0, wherein T m is the melting temperature of the ultra high molecular weight polyethylene polymer.

[0019] In some aspects of the present invention, the powder bulk density of the ultra-high molecular weight polyethylene polymer is 200-700 kg / m 3 , preferably 250-650kg / m 3 , preferably 300-450kg / m 3 . For the purposes of the present invention, the powder bulk density of the ultra-high molecular weight polyethylene polymer can be measured according to the procedure outlined in ASTM D1895 / A. In some cases, the powder bulk density of the ultra-high molecular weight polyethylene polymer is measured according to the procedure outlined in ASTM D1895 / A, wherein adjustments include passing a scraper through the ultra-high molecular weight polyethylene polymer to promote polymer flow. As will be appreciated by those skilled in the art, the UHMWPE polymer of the present invention exhibits excellent powder morphology, as indicated by its high bulk density, compared to existing disentangled UHMWPE polymers known in the art. The high bulk density of the UHMWPE polymer ensures that it is easy to process, particularly when the polymer processing involves powder sintering, and also ensures that the polymer powder is easy to handle and store.

[0020] In some aspects of the invention, the intrinsic viscosity (IV) is 8.0-100.0 dl / g, preferably 10.0-70.0 dl / g, preferably 20.0-65.0 dl / g, as measured by ASTM D4020. The intrinsic viscosity data can be used to determine that the polyethylene polymer is a high molecular weight polyethylene. The viscosity value can then be converted to a molecular weight value using the Mark Houwink equation. In some aspects of the invention, the viscosity average molecular weight (Mv) of the UHMWPE polymer is greater than 500,000 g / mol, preferably greater than 750,000 g / mol, and more preferably greater than 1,000,000 g / mol.

[0021] In some aspects of the present invention, when the stretching temperature is ≥ T m When stretched at -30°C, the sample prepared from the ultra-high molecular weight polyethylene can be stretched at a total stretch ratio of 50.0-300.0, preferably 60.0-250.0, preferably 65.0-230.0 in the absence of solvent, wherein T m is the melting temperature of the ultra-high molecular weight polyethylene polymer. As will be appreciated by those skilled in the art, the ability to stretch a sample prepared from a UHMWPE polymer below its melting temperature is referred to as solid state stretching and is indicative of the performance characteristics of the polymer. The term "sample" as used in the present invention refers to a calendered, compression molded or rolled film or tape or fiber obtained from the UHMWPE polymer powder of the present invention after compacting the polymer powder, whereby the sample can subsequently be solid state stretched.

[0022] In some embodiments of the present invention, the ultra-high molecular weight polyethylene polymer is stretched at a temperature ≥ T m –30℃, preferably ≥T m –15℃, preferably ≥T m –10℃, preferably ≥T m In some embodiments of the present invention, the ultra-high molecular weight polyethylene polymer is stretched at T m –30℃ to T m Any stretching temperature between T m –15℃ to T m Any temperature between T m –10℃ to T m Any temperature between T m –5℃ and T m The melting temperature of the polymer can be determined using differential scanning calorimetry (DSC) as described in Example 1 of the present invention. The ability to stretch samples prepared from UHMWPE polymers over such a wide stretching temperature range and at high stretch ratios provides a wide processing window for the production of fibers, tapes and filaments.

[0023] In some aspects of the present invention, the UHMWPE polymer is a disentangled UHMWPE polymer. The term "disentangled UHMWPE polymer" as used in the present invention refers to the polymer being used to prepare a sample, wherein the sample can be stretched at a stretch ratio greater than 50 and a stretching temperature as low as T in the absence of a solvent. m –30℃ solid state stretching. Usually, when the stretching temperature is as low as T mAt -30°C, articles such as fibers and filaments having high strength and modulus can be prepared without the need for complex steps including solution spinning, casting techniques, dissolution, precipitation, extraction and drying. The term "stretching in the absence of solvent" as used herein refers to the implementation of sample stretching in the solid state without the need for solution or gel spinning techniques or solution crystallization. For the purpose of solid-state stretching described in the present invention, UHMWPE polymer powder can be compacted and processed in the solid state for stretching.

[0024] In some embodiments of the present invention, the UHMWPE polymer powder has a suitable particle size, indicating that the particle morphology is improved. In some aspects of the present invention, the ultra-high molecular weight polyethylene polymer has an average particle size (D) measured according to ISO-13320 (2009). 50 ) is 50.0-250.0 μm, preferably 60.0-200.0 μm ultra-high molecular weight polyethylene polymer powder. The average particle size (D 50 ) can be determined by using a laser light scattering method involving hexane as a diluent and using a Malvern Mastersizer apparatus.

[0025] In some aspects of the invention, the ultra high molecular weight polyethylene polymer is a copolymer comprising:

[0026] At least 95.0 wt%, preferably at least 98.0 wt%, preferably at least 99.0 wt%, preferably at least 99.9 wt% of the moieties derived from ethylene, based on the total weight of the ultra-high molecular weight polyethylene polymer; and

[0027] Based on the total weight of the ultra-high molecular weight polyethylene polymer, up to 5.0 wt%, preferably up to 2.0 wt%, preferably up to 1.0 wt%, preferably up to 0.1 wt% of a portion derived from one or more α-olefins, the α-olefins being selected from propylene, 1-butene, 4-methyl-1-pentene, 1-hexene and 1-octene, preferably selected from propylene, 1-butene, 1-hexene and 1-octene.

[0028] In some embodiments of the invention, the ultra high molecular weight polyethylene polymer is a copolymer comprising 95.0-100 wt% of moieties derived from ethylene, based on its total weight. In some embodiments of the invention, the ultra high molecular weight polyethylene polymer is a copolymer comprising 0.1-5.0 wt% of moieties derived from one or more alpha-olefins, based on its total weight.

[0029] In some aspects of the invention, the invention relates to discrete transition metal complexes on a particulate solid support material for producing ultra-high molecular weight polyethylene polymers. In some aspects of the invention, the invention relates to a catalyst composition for preparing the ultra-high molecular weight polyethylene polymer of the invention, comprising:

[0030] a. By general formula (I) L n MX (k-n) A transition metal complex represented by

[0031] L represents an organic ligand,

[0032] M represents transition metal,

[0033] X represents a substituent selected from the group consisting of fluorine, chlorine, bromine or iodine, an alkyl group having 1 to 20 carbon atoms, an aralkyl group having 1 to 20 carbon atoms, a dialkylamino group having 1 to 20 carbon atoms or an alkoxy group having 1 to 20 carbon atoms,

[0034] k represents a positive integer and is the valence of the transition metal 'M',

[0035] n is an integer defined by 1≤n≤k; and

[0036] b. A particulate catalyst support comprising particles having a volume median particle size of at least 0.3 μm, preferably at least 1.0 μm, wherein the transition metal complex is supported on the particulate catalyst support.

[0037] In some aspects of the present invention, the present invention relates to an ultra-high molecular weight polyethylene having the following properties:

[0038] The bulk density of the powder is at least 200 kg / m 3 , preferably at least 300 kg / m 3 ;

[0039] An intrinsic viscosity (IV) of at least 8.0 dl / g, preferably at least 10.0 dl / g, as measured by ASTM D4020; and

[0040] When the stretching temperature ≥ T m When stretched at -30°C, a sample prepared from the ultra-high molecular weight polyethylene can be stretched in the absence of a solvent at a total stretch ratio of at least 50.0, preferably at least 90.0, wherein T m is the melting temperature of the ultra-high molecular weight polyethylene polymer,

[0041] The ultra-high molecular weight polyethylene is produced by a catalyst comprising:

[0042] a. By general formula (I) L n MX (k-n) A transition metal complex represented by

[0043] L represents an organic ligand,

[0044] M represents transition metal,

[0045] X represents a substituent selected from the group consisting of fluorine, chlorine, bromine or iodine, an alkyl group having 1 to 20 carbon atoms, an aralkyl group having 1 to 20 carbon atoms, a dialkylamino group having 1 to 20 carbon atoms or an alkoxy group having 1 to 20 carbon atoms,

[0046] k represents a positive integer and is the valence of the transition metal 'M',

[0047] n is an integer defined by 1≤n≤k; and

[0048] b. A particulate catalyst support comprising particles having a volume median particle size of at least 0.3 μm, preferably at least 1.0 μm, wherein the transition metal complex is supported on the particulate catalyst support.

[0049] In some aspects of the present invention, the particulate catalyst support comprises a particulate organoaluminum selected from methylaluminoxane (MAO), isobutylaluminoxane, methylisobutylaluminoxane, and ethylisobutylaluminoxane, and the particulate organoaluminum is preferably methylaluminoxane (MAO). In some embodiments of the present invention, the particulate catalyst support comprises particles having a volume-based median particle size of 0.3-200.0 μm, preferably 1.0-100.0 μm, preferably 5.0-50.0 μm. The particle size of the support can be measured using a Mastersizer 2000 Hydro S of Malvern Instrument Ltd. in a dry nitrogen atmosphere using a laser diffraction / scattering method.

[0050] In some preferred aspects of the present invention, methylaluminoxane (MAO) is a morphology-controlled solid methylaluminoxane (MAO), as described in patents US8404880, US9340630 and US2018 / 0355077 (assigned to Tosoh) or WO03 / 051934 (assigned to Borealis). The morphology-controlled solid MAO includes a suspension of solid methylaluminoxane (MAO) particles in a hydrocarbon diluent. The inventors found that when this morphology-controlled solid MAO is used as a catalyst support, the obtained UHMWPE polymer has a well-defined morphology, which is in sharp contrast to dissolved MAO (MAO dissolved in hydrocarbon solvents and generally used as a co-catalyst rather than a catalyst support). This conclusion is also confirmed by the polymers obtained by the embodiments of the present invention. The inventors surprisingly found that when a catalyst containing a morphology-controlled solid MAO is applied, the obtained UHMWPE polymer is a disentangled UHMWPE polymer.

[0051] In some embodiments of the present invention, the organic ligand (L) is selected from substituted or unsubstituted cyclopentadienyl, indenyl, fluorenyl, naphthyl, phenoxy, imine, amine, pyridyl, phenoxy-imine, phenoxy-amine, phenoxy ether, quinolyl-indenyl, phenoxy ether, benzyl, tert-butylbenzene, neopentyl or a combination thereof. The organic ligand (L) is preferably selected from phenoxy-imine, phenoxy-amine and phenoxy ether. In some embodiments of the present invention, the transition metal complex is one having an organic ligand (L) based on a cyclopentadienyl derivative attached to a pyridyl or quinolyl moiety, preferably dichloro-1-(8-quinolyl-indenyl) chromium complex.

[0052] In some embodiments of the present invention, the transition metal (M) is a metal selected from Group IV of the Mendeleev Periodic Table, and the transition metal (M) is preferably titanium. In some embodiments of the present invention, the particulate catalyst support is an organoaluminum, and the molar ratio of aluminum metal to transition metal complex present in the particulate catalyst support is 50-5000, preferably 75-1000, preferably 100-800.

[0053] In some preferred embodiments of the present invention, the catalyst composition comprises diphenoxyimine titanium dichloride supported on particulate methylaluminoxane (MAO) particles, wherein the volume-based median particle size of the particulate methylaluminoxane (MAO) particles is at least 0.3 μm, preferably at least 1.0 μm, and preferably at least 5.0 μm. The compound diphenoxyimine titanium dichloride may be referred to as the "FI compound". In some embodiments of the present invention, the active catalyst component is formed by activating the FI compound with particulate methylaluminoxane (MAO). Without wishing to be bound by any particular theory, the methylaluminoxane (MAO) particles act as a catalyst support and a co-catalyst activator.

[0054] The improved properties of the polymers produced by the methylaluminoxane (MAO) supported FI compound catalysts are particularly surprising compared to the performance of the nanoparticle supported FI compound catalysts reported in the published patent WO2010 / 139720, where the small size of the nanoparticles is used to limit the interaction of the catalyst active sites, thereby reducing polymer entanglement. However, the mechanical strength and modulus of the polymers described in WO2010 / 139720 are comparable to low entanglement UHMWPE polymers, which are lower than the polymers obtained by the present invention.

[0055] In some embodiments of the present invention, the catalyst composition further comprises a scavenger additive selected from an organolithium compound, an organomagnesium compound, an organoaluminum compound, an organozinc compound, and mixtures thereof. Non-limiting examples of organoaluminum compounds include trimethylaluminum, triethylaluminum, triisopropylaluminum, tri-n-propylaluminum, triisobutylaluminum, tri-n-butylaluminum, tri-tert-butylaluminum, isoprenylaluminum, tripentylaluminum, tri-n-hexylaluminum, trioctylaluminum, dimethylaluminum ethoxy, diethylaluminum ethoxy, diisopropylaluminum ethoxy, di-n-propylaluminum ethoxy, diisobutylaluminum ethoxy and di-n-butylaluminum ethoxy, dimethylaluminum hydride, diethylaluminum hydride, diisopropylaluminum hydride, di-n-propylaluminum hydride, diisobutylaluminum hydride and di-n-butylaluminum hydride, soluble aluminoxane, granular aluminoxane, and mixtures thereof. Without wishing to be limited by any theory, scavenger additives help to remove impurities in the polymerization system that would otherwise have an adverse effect on catalyst performance. In some embodiments of the present invention, the organoaluminum compound can be combined with a compound containing at least one active hydrogen and capable of reacting with the organoaluminum compound. Non-limiting examples of such compounds having at least one active hydrogen include alcohol compounds, silanol compounds, and amino compounds. Suitable alcohol compounds include monophenol compounds, such as butylated hydroxytoluene (BHT, 2,6-di-tert-butyl-4-methylphenol), 2,6-di-tert-butyl-phenol, or alpha-tocopherol (vitamin E). Non-limiting examples of amine compounds include cyclohexylamine or alkylamines.

[0056] The ultra-high molecular weight polyethylene polymer of the present invention can be produced using a gas phase process or a slurry process, as long as the polymer is formed as a granular solid powder. The production method of polyethylene is summarized in Andrew Peacock's "Handbook of Polyethylene" (2000; Dekker; ISBN0824795466) pages 43-66. The polymerization reaction can be carried out in the gas phase or in bulk in the absence of an organic solvent, or in a liquid slurry in the presence of an organic diluent. The polymerization can be carried out in an intermittent, semi-intermittent or continuous manner. In some aspects of the present invention, the present invention relates to a method for preparing the ultra-high molecular weight polyethylene polymer of the present invention, the method comprising the step of polymerizing ethylene and optionally one or more alpha-olefins in the presence of a supported catalyst composition and optionally in the presence of hydrogen.

[0057] In some aspects of the invention, the polymerization temperature is 0-140°C, preferably 10-90°C, preferably 25-80°C. It is sufficient that the pressure of the monomers during the polymerization is atmospheric pressure, more preferably 1-50 bar (1 bar = 100000 Pa). In some aspects of the invention, after polymerization, any residual reactive components of the catalyst or scavenger present in the polymerization reactor can be deactivated by adding a so-called "killer" to the polymerization vessel. Such killers are well known in the art and are chemical components that deactivate catalysts and scavengers. Non-limiting examples of killers include oxygen, water, alcohols, stearates or amines.

[0058] In some aspects of the present invention, the present invention relates to articles prepared from the ultra-high molecular weight polyethylene of the present invention having the following properties:

[0059] The bulk density of the powder is at least 200 kg / m 3 , preferably at least 300 kg / m 3 ;

[0060] An intrinsic viscosity (IV) of at least 8.0 dl / g, preferably at least 10.0 dl / g, as measured by ASTM D4020; and

[0061] When the stretching temperature ≥ T m When stretched at -30°C, a sample prepared from the ultra-high molecular weight polyethylene can be stretched in the absence of a solvent at a total stretch ratio of at least 50.0, preferably at least 90.0, wherein T m is the melting temperature of the ultra high molecular weight polyethylene polymer.

[0062] In some embodiments of the present invention, the article is a stretched article, characterized in that the breaking strength of the stretched article is related to the total stretch ratio (DR) for preparing the stretched article by the following formula (I):

[0063] BT>α*ln(DR)–β(Formula I)

[0064] Wherein the total draw ratio (DR) is at least 50.0, the breaking strength (BT) is expressed in N / tex, 0.835≤α≤0.881, 1.787≤β≤1.887, and the ratio of α / β is 0.467.

[0065] In some preferred embodiments of the present invention, the article is a stretched article, characterized in that the breaking strength of the stretched article is related to the total stretch ratio (DR) for preparing the stretched article by the following formula (II):

[0066] BT>0.835*ln(DR)–1.787 (Formula II).

[0067] As is apparent from formulas (I) and (II), articles made from ultra-high molecular weight polyethylene polymers have high strength and can be made at high draw ratios. In some aspects of the invention, the article has a tensile modulus of 2.0-9.0 GPa, such as 3.0-8.0 GPa, when measured according to the procedure described in ASTM D7744 / D7744M-11.

[0068] In some aspects of the present invention, the present invention relates to a method for preparing the stretched article of the present invention, comprising the steps of:

[0069] Compacting ultra-high molecular weight polyethylene polymer powder into a film sample having a length of L1; and

[0070] Rolling and / or calendering the film sample into a rolled film sample with a length of L2, and a stretching ratio of L2 / L1≥2; and

[0071] At stretching temperature ≥ T m The rolled film sample is stretched at -30°C to form a stretched product with a length of L3, wherein T m is the melting temperature of the ultra high molecular weight polyethylene polymer, and wherein the rolled film sample is stretched at a stretch ratio L3 / L2 such that the total stretch ratio L3 / L1≥50.

[0072] The total stretch ratio (L3 / L1) is defined by the product of L2 / L1 and L3 / L2. To determine L2 / L1 and L3 / L2, an optical microscope can be used to determine the cross section of the stretched article obtained in each step. The concept of volume conservation can be used, applying the equation L n =w n *t n Determine the cross section, where 'L n ' is the sample length, 'w n ' is the sample width and 't n ' is the sample thickness, where 'n' can be 1, 2 or 3.

[0073] The compaction can be carried out at a temperature T m –30℃ to T m between T m –15℃ to T m The compaction pressure can be, for example, >100 bar and <300 bar, preferably >150 bar and <250 bar. The pressing can be, for example, carried out at a L2 / L1 of 2-5, preferably 3-4. The rolling can be, for example, carried out at a temperature of T m –30℃ to T m between T m –15℃ to T m The temperature during rolling is preferably lower than the temperature during compacting.

[0074] In some aspects of the present invention, the present invention relates to an ultra-high molecular weight polyethylene having the following properties:

[0075] The bulk density of the powder is at least 200 kg / m 3 , preferably at least 300 kg / m 3 ;

[0076] An intrinsic viscosity (IV) of at least 8.0 dl / g, preferably at least 10.0 dl / g, as measured by ASTM D4020; and

[0077] When the stretching temperature ≥ T m When stretched at -30°C, a sample prepared from the ultra-high molecular weight polyethylene can be stretched in the absence of a solvent at a total stretch ratio of at least 50.0, preferably at least 90.0, wherein T m is the melting temperature of the ultra-high molecular weight polyethylene polymer;

[0078] The ultra-high molecular weight polyethylene is produced using a catalyst, and the catalyst comprises:

[0079] a. By general formula (I) L n MX (k-n) A transition metal complex represented by

[0080] L represents an organic ligand,

[0081] M represents transition metal,

[0082] X represents a substituent selected from the group consisting of fluorine, chlorine, bromine or iodine, an alkyl group having 1 to 20 carbon atoms, an aralkyl group having 1 to 20 carbon atoms, a dialkylamino group having 1 to 20 carbon atoms or an alkoxy group having 1 to 20 carbon atoms,

[0083] k represents a positive integer and is the valence of the transition metal 'M',

[0084] n is an integer defined by 1≤n≤k; and

[0085] b. a particulate catalyst support comprising particles having a volume median particle size of at least 0.3 μm, preferably at least 1.0 μm, wherein the transition metal complex is supported on the particulate catalyst support;

[0086] Furthermore, the article prepared from the ultra-high molecular weight polyethylene is a stretched article, characterized in that the breaking strength of the stretched article is related to the total stretching ratio (DR) for preparing the stretched article by the following formula (I):

[0087] BT>α*ln(DR)–β (Formula I)

[0088] Wherein the total draw ratio (DR) is at least 50.0, the breaking strength (BT) is expressed in N / tex, 0.835≤α≤0.881, 1.787≤β≤1.887, and the ratio of α / β is 0.467.

[0089] In certain embodiments, the article can be, for example, a fiber, a film, a tape, or a yarn.

[0090] Example

[0091] Specific examples demonstrating some embodiments of the present invention are given below. These examples are for illustrative purposes only and are not intended to limit the present invention.

[0092] Embodiment 1 (present invention)

[0093] Purpose : The properties of UHMWPE polymers produced by polymerizing ethylene in the absence of hydrogen using a diphenoxyimine titanium complex [3-tBu-2-O-C6H3CH=N(C6F5)]2TiCl2 (abbreviated as FI) supported on particulate methylaluminoxane (MAO) were evaluated.

[0094] Catalyst system used: used for the purpose of Example 1

[0095] Table 1: Catalyst system

[0096]

[0097] Catalyst preparation and polymerization steps A series of ethylene polymerizations were carried out using FI compounds as discrete transition metal complexes supported on granular methylaluminoxane (sMAO) as a granular support, using triisobutylaluminum as a scavenger. The polymerization steps were carried out in a 10-liter stirred autoclave using 5 liters of pure hexane as a diluent. Triisobutylaluminum (1 mmol) as a scavenger was added to 5 liters of pure hexane and the stirrer was set to 1000 RPM. The mixture was heated to the desired polymerization temperature (T pol ) and pressurized with ethylene to the desired pressure. The total pressure of the reactor is determined by ethylene (P C2 ) and the partial pressure of hexane.

[0098] In a separate glass container, under an inert atmosphere, a solution containing a predetermined amount of discrete transition metal complex (FI compound) is premixed with a suspension containing a predetermined amount of particulate support (sMAO). Mixing is performed by manually shaking the resulting suspension. The premixing time is generally less than 10 minutes. Subsequently, the resulting suspension containing the supported catalyst is injected into the reactor through a pressurized gate, and the gate is rinsed with hexane. The temperature is maintained at the desired set point by a water-cooled thermostat, and the pressure is kept constant by feeding ethylene through a mass flow meter. The mass flow meter indicates the differential and cumulative amount of ethylene absorbed by the polymerization reaction (C2 dose). When the desired amount of ethylene has been added to the reactor, the reaction is stopped. The reaction is stopped by decompressing and cooling the reactor and reducing the agitator speed. The reactor contents are then passed through a filter. The wet polymer powder is then collected, then vacuum dried at 50°C, weighed and analyzed. The polymerization conditions are varied according to the pressure, C2 dose and the molar ratio of aluminum to FI compound in sMAO to obtain several samples represented by sample identification codes, respectively. The corresponding polymer powder samples are identified based on the sample codes provided below.

[0099] The implemented aggregation conditions are summarized as follows:

[0100] Table 2: Polymerization conditions

[0101]

[0102]

[0103] Polymer Evaluation : The properties of the obtained polymer samples were evaluated with respect to powder bulk density, intrinsic viscosity, crystallinity, melting temperature and maximum draw ratio at specific stretching temperatures of 125°C and 135°C.

[0104] Powder bulk density : The bulk density of the UHMWPE polymer powder obtained after polymerization was measured according to the procedure specified in standard ASTM D1895 / A. The procedure consists in filling a calibrated 100 mL steel cylinder with the polymer powder and then measuring the weight of the cylinder with a calibrated polymer volume of 100 mL. If the polymer powder does not flow spontaneously, the procedure is adjusted by passing a spatula through the powder to promote flow through the opening of a metering container mounted above the 100 mL calibrated steel container.

[0105] Intrinsic viscosity (IV) : The intrinsic viscosity of a dilute solution of a UHMWPE polymer is measured as described in standard ASTM D4020, involving a dilute solution of a UHMWPE polymer in decalin at a temperature of 135°C.

[0106] Differential scanning calorimetry (DSC) was used to determine the crystallinity (Xc) and melting temperature (T m ): To reduce the thermal hysteresis caused by the sample, the weight of each sample was kept within 1.5 ± 0.2 mg. During the measurement, nitrogen was continuously purged at 50 mL / min to prevent sample degradation. The thermal process adopted during the measurement included: 1) first heating from -40 °C to 180 °C at 10 °C / min; 2) a 5-minute annealing step at 180 °C to eliminate the accumulated heat of the powder for 5 minutes; 3) cooling from 180 °C to -40 °C at 10 °C / min; and 4) finally heating from -40 °C to 180 °C.

[0107] The crystalline volume fraction (Xc) was evaluated from the melting endotherm obtained in 1) by applying the ratio between the enthalpy measured during the heating operation and the equilibrium melting enthalpy of polyethylene (293 J / g). Melting temperature (T m ) takes the maximum value of the melting endotherm obtained in step 1) of this process.

[0108] Application of high draw ratios to prepare tapes : The polymer powder thus obtained is first converted into a film sample and then formed into a tape according to the following process steps: (i) compacting the ultra-high molecular weight polyethylene polymer powder into a film sample, (ii) rolling and / or calendering the film sample to form a rolled film sample, and (iii) subsequently stretching the rolled film sample into a tape.

[0109] Compaction : Nascent powder was first compacted into a film sample at 125°C (ie below the melting point) and a pressure of 200 bar.

[0110] Rolling / calendering : The film sample was then pre-stretched to about 3-4 times its initial length (L2 / L1 was 3-4) in two separate steps using calendering rollers at a temperature of 120°C to improve the consistency of the film and obtain a rolled film sample.

[0111] Solid state stretching: The rolled film sample obtained after rolling / calendering is solid-state stretched using a stretcher at a suitable stretch ratio (L3 / L2) to form a tape, wherein the total stretch ratio (L3 / L1) is maintained greater than 50.

[0112] To determine the maximum total stretch ratio (λ max ) in the solid-state stretching process Dog-bone shaped tensile strip specimens (5 mm width and 10.5 mm grip-to-grip length) were cut from the obtained strips by using a bent lever cutter with a special punch. A Zwick Z010 universal tensile testing machine equipped with pneumatic grips, a 1 kN load cell and a thermostatically controlled temperature chamber was used for the test. -1 The solid-state tensile test was carried out at a constant initial strain rate. The tensile test was carried out at two different stretching temperatures (both below the melting point of the UHMWPE polymer solidified tape: 125°C and 135°C) until the sample broke or the maximum total stretch ratio (λmax ). max The value of represents the characteristic of the polymer and is used to evaluate the degree of entanglement of the polymer.

[0113] The results obtained from the analysis are provided in Table 3 below.

[0114] Table 3: Polymer evaluation

[0115]

[0116] It is obvious from the results shown in Table 3 that the tape samples prepared from UHMWPE polymer can be stretched at a temperature (λ max 125 ° C), with a total draw ratio higher than 50 and in some cases higher than 90, without the need for solvent to dissolve the polymer. The powder bulk density of the UHMWPE polymer obtained by polymerization is relatively high (greater than 20g / 100ml or 200kg / m 3 ), in some cases greater than 350kg / m 3 (35.1 g / 100 ml, as reported for sample No. 20190926AKO1). During the polymerization process for preparing the UHMWPE polymer, no reactor fouling was observed. In addition, it was observed that the polymer sample produced by Example 1 had an excellent balance between high crystallinity (>70%), ideal bulk density, and suitable stretchability.

[0117] With test plan : For tape testing purposes, by stretching at a ratio below λ max The strip samples of sample No. 20190925AKO1, 20190904AKO2, 20190905AKO1, 20190905AKO2, 20190923AKO2, 20190926AKO1 prepared as described above were evaluated by stretching. The uniaxially stretched strips stretched at different stretch ratios were tested at room temperature (25°C) using a Zwick Z010 universal tensile testing machine. A side-moving pneumatic clamp with a flat jaw surface was used to prevent the sliding and breaking of the clamp. The test was carried out at a constant extension rate (crosshead movement rate) of 50 mm / min. The breaking strength (or tensile strength) and modulus (fragment between 0.3-0.4 N / tex) were determined by the force and displacement between the jaws. The strips that broke at the clamp were discarded.

[0118] The width and thickness of the ribbons were determined by direct measurement using an optical microscope after calibrating the image with a micrometer-sized grid. The total stretch ratio of the ribbon was calculated by taking the ratio of the cross section of the ribbon sample after stretching to the cross section before stretching. The modulus and strength values ​​are expressed in GPa (10 6 N / m 2) was obtained, and then divided by the density of crystalline PE (0.98 kg / m3) to convert it into N / tex. The results are listed in the following Table 4:

[0119] Table 4: With evaluation

[0120]

[0121]

[0122] As is evident from the results of Example 1, the polymer of the present invention is a disentangled UHMWPE polymer having a bulk density comparable to that of a low entangled UHMWPE polymer, but with superior break strength. The results provided in Table 4 show that the tapes prepared from the UHMWPE polymer of Example 1 can be solid state stretched at high draw ratios (draw ratio > 50.0) while maintaining excellent mechanical properties, as shown by the break strength and tensile modulus values. Specifically, the tapes / samples obtained from Example 1 exhibit high break strength even at high total draw ratios, and satisfy the relationship of Formula II. In addition, relative to the tapes / samples prepared from Comparative Example 3 ( Figure 3 ) and Example 4 ( Figure 4 ) The morphology of the polymer powder obtained, Figure 2 Scanning electron microscopy (SEM) image of (a) shows the well-defined powder shape and morphology.

[0123] Embodiment 2 (present invention)

[0124] Purpose Example 2 has the same purpose as Example 1, except that the ethylene polymerization is carried out in the presence of hydrogen, which is different from the method described in Example 1 in which the ethylene polymerization is carried out in the absence of hydrogen. The UHMWPE polymer and subsequent tape obtained from Example 2 (sample code: 20191218AKO2) are compared with the polymer and tape of Example 1 represented by sample code 20190925AKO2.

[0125] The catalyst used for the purpose of Example 2 is the same as that of Example 1. The polymerization parameters of Example 2 are shown in Table 5 below:

[0126] Table 5: Polymerization conditions

[0127] Example No. Sample code No FI concentration sMAO / FI <![CDATA[Pressure C2 > Polymerization temperature <![CDATA[C2 dose]]> <![CDATA[pH2 / pC2]]> Aggregation time mmol / L mol / mol bar ℃ gram bar / bar min Example 2 20191218AKO2 0.015 320 1.5 30 280 0.00275 124 Example 1 20190925AKO2 0.010 800 1 30 250 0 127

[0128] The analysis of the polymers is given in Table 6 below:

[0129] Table 6: Polymer Evaluation

[0130] Example No. Sample code No Xc DSC <![CDATA[T m ]]> <![CDATA[λ max 125℃]]> <![CDATA[λ max 135℃]]> IV <![CDATA[% wt ]]> ℃ [mm / mm] [mm / mm] dl / g Example 2 20191218AKO2 77 141.2 74±6 >90 25.2 Example 1 20190925AKO2 73 141.6 63±2 >90 44.0

[0131] From these experiments it is evident that hydrogen significantly reduces the molecular weight of the polymer as indicated by the reduction in intrinsic viscosity (IV). In addition, the bulk density of the polymer thus obtained is comparable to that obtained in Example 1.

[0132] Several tapes were prepared from the polymer sample obtained in Example 2 (sample code 20191218AKO2) at a maximum total draw ratio (λ max ) were stretched at different total draw ratios (DR) and subsequently their mechanical strength (breaking strength and tensile modulus) were evaluated.

[0133] Table 7: With evaluation

[0134] Sample No: <![CDATA[T m ]]> Stretching temperature Total stretch ratio Breaking strength Tensile modulus ℃ ℃ mm / mm N / tex N / tex 20191218AKO2 141.2 135 60 2.20 111.76 20191218AKO2 141.2 135 64 2.46 133.56 20191218AKO2 141.2 135 67 2.27 112.83

[0135] It is evident from the data provided in Table 7 that the application of solid state stretching allows the preparation of tapes having very good properties of both breaking strength and tensile modulus.

[0136] Example 3 (Comparative Example)

[0137] Purpose : The purpose of Example 3 was to compare the performance of silica supported catalysts in the production of UHMWPE polymers and tapes prepared from said polymers.

[0138] The catalyst system used For the purpose of Example 3, a FI catalyst system supported on a granular silica support was used instead of a granular MAO support:

[0139] Table 8: Catalyst system

[0140]

[0141] The catalyst preparation includes premixing a discrete transition metal complex (FI compound) with a solution of methylaluminoxane (MAO) in toluene. Subsequently, the catalyst premix is ​​contacted with a granular ES757 silica support. The molar ratio of aluminum in the activator to the active catalyst component (MAO / FI molar ratio) is maintained at 200. 3 grams of supported FI catalyst system are used for each polymerization experiment.

[0142] The polymerization conditions are given in Table 9:

[0143] Table 9: Polymerization conditions

[0144] Sample code No: MAO / FI <![CDATA[Pressure C2]]> Polymerization temperature <![CDATA[C2 dose]]> Aggregation time bar ℃ gram min 20191018AKO2 200 3.5 30 250 75 20191127AKO2 200 1.5 30 120 75

[0145] The obtained UHMWPE polymer was evaluated and the results are shown below:

[0146] Table 10: Polymer Evaluation

[0147]

[0148] No reactor fouling was observed and the bulk density of the polymer powder obtained was acceptable. However, a maximum draw ratio (λ max 125°C) was below 50, which was lower than the desired value because the produced tape could not achieve the desired strength and modulus. Subsequently, tapes were prepared and stretched at different stretch ratios below λmax, and the strength of the tapes thus obtained was evaluated.

[0149] Table 11: With evaluation

[0150]

[0151]

[0152] It is obvious from Comparative Example 3 that the tape cannot be stretched to the desired total stretch ratio, and the strength of the stretched sample only reaches a maximum breaking strength of 1.3 N / tex (20191127AKO2), which is lower than the maximum breaking strength achieved by the tapes produced in Examples 1 and 2. In addition, unlike Examples 1-2 of the present invention, the tape prepared in Example 3 can only be solid-state stretched at a high total stretch ratio at a temperature (135°C) several degrees below the melting temperature of the polymer. At a stretching temperature of 125°C, the desired stretch ratio cannot be achieved. In addition, Figure 3 It can be seen that the powder morphology of the obtained polymer is also not as well defined as that obtained from Example 1 of the present invention.

[0153] Example 4 (Comparative Example)

[0154] Purpose : The purpose of Example 4 is to investigate the performance of an unsupported FI catalyst compound in the production of UHMWPE polymer and tapes.

[0155] The catalyst system used : For the purpose of Example 4, an unsupported FI catalyst system was used instead of the particulate support:

[0156] Table 12: Catalyst system

[0157]

[0158] The polymerization conditions and polymer properties are given in Table 13. For the purpose of Example 4, two samples were evaluated: (i) sample code PDR-7309-6 and (ii) sample code ACE-170922-uh1. The polymerization conditions applied and the polymers thus obtained were evaluated and the results are given in Table 13:

[0159] Table 13: Polymerization conditions and polymer evaluation

[0160]

[0161] Severe reactor fouling was observed during the polymerization of both samples, as shown by polymer deposition on the reactor walls and the stirrer. In addition, the obtained UHMWPE polymer exhibited poor morphology, as shown by the low bulk density values ​​of the polymer. Tapes were prepared from the obtained polymer samples at different total draw ratios. The results of the tape evaluation are given below:

[0162] Table 14: Polymerization conditions and polymer evaluation

[0163] Sample code No <![CDATA[T m ]]> Stretching temperature Total stretch ratio Breaking strength Tensile modulus ℃ ℃ mm / mm N / tex N / tex PDR-7309-6 142.9 135 35 1.70 65.82 PDR-7309-6 142.9 135 30 1.73 57.57 PDR-7309-6 142.9 135 37 1.99 74.77 PDR-7309-6 142.9 135 37 2.04 84.70 PDR-7309-6 142.9 135 47 2.30 86.20 PDR-7309-6 142.9 135 69 2.57 135.73 PDR-7309-6 142.9 135 67 2.58 143.48 PDR-7309-6 142.9 135 71 2.71 143.86 PDR-7309-6 142.9 135 62 2.78 141.29 PDR-7309-6 142.9 135 109 2.94 196.75 PDR-7309-6 142.9 135 102 2.98 166.78 PDR-7309-6 142.9 135 100 3.29 192.23 ACE-170922-uh1 142.1 135 200 4.56 161.12 ACE-170922-uh1 142.1 135 93 2.88 80.65 ACE-170922-uh1 142.1 135 74 2.21 75.46 ACE-170922-uh1 142.1 135 153 4.13 140.93 ACE-170922-uh1 142.1 135 186 4.11 150.68

[0164] Although the tapes made from the polymers exhibit acceptable mechanical strength and modulus, it is difficult to scale up the production to industrial systems due to severe reactor fouling and poor powder morphology properties. Figure 4 As shown in the scanning electron microscope (SEM) images, the obtained polymer powder exhibited irregular powder shape and morphology.

[0165] Summarize : Table 15 below summarizes the results obtained for the key parameters implemented for Examples 1-4.

[0166] Table 15: Summary of results of Examples 1-4

[0167]

[0168] As is apparent from the qualitative summary provided in Table 15, Examples 1 and 2 of the present invention can be produced without severe reactor fouling while providing a balance of all desirable properties. Figure 1 It is shown that Examples 1-2 of the present invention provide tapes with high strength and modulus that can be stretched at high draw ratios. Although the tape provided by Example 4 also has high strength (breaking strength), the bulk density of the polymer is poor, and the production of the polymer causes severe fouling of the reactor, making the total polymer output of the method of Example 4 unfeasible on an industrial scale.

Claims

1. An ultra-high molecular weight polyethylene polymer having the following properties: Powder bulk density of at least 200 kg / m3 as measured by ASTM D1895 / A-1996, reapproved 2010-e1 3 ; An intrinsic viscosity IV of at least 10.0 dl / g as measured according to ASTM D4020-2005; A degree of crystallinity Xc greater than 70% as determined by differential scanning calorimetry (DSC); and When the stretching temperature T m –30℃ to T m When stretched between two stretching steps, a sample prepared from the ultra-high molecular weight polyethylene can be stretched at a total stretch ratio of at least 50.0 in the absence of a solvent, wherein T m is the melting temperature of the ultra-high molecular weight polyethylene polymer; wherein the ultra-high molecular weight polyethylene polymer is produced from ethylene and optionally one or more α-olefins in the presence of a catalyst composition comprising: a. By general formula (I) L n MX (k-n) A transition metal complex represented by L represents an organic ligand, wherein the organic ligand L is selected from phenoxyimine, phenoxyamine and phenoxyether, M represents a transition metal, wherein the transition metal M is a metal selected from Group IV of the Mendeleev Periodic Table of Elements, X represents a substituent selected from the group consisting of fluorine, chlorine, bromine or iodine, an alkyl group having 1 to 20 carbon atoms, an aralkyl group having 1 to 20 carbon atoms, a dialkylamino group having 1 to 20 carbon atoms or an alkoxy group having 1 to 20 carbon atoms, k represents a positive integer and is the valence of the transition metal 'M', n is an integer defined by 1≤n≤k; and b. a particulate catalyst support comprising particles having a volume median particle size of 0.3-200.0 μm, wherein the transition metal complex is carried on the particulate catalyst support; The particulate catalyst carrier comprises a particulate organic aluminum selected from methylaluminoxane MAO, isobutylaluminoxane, methylisobutylaluminoxane, and ethylisobutylaluminoxane.

2. The ultra-high molecular weight polyethylene polymer according to claim 1, wherein the ultra-high molecular weight polyethylene polymer has an average particle size D measured according to ISO-13320-2009. 50 It is an ultra-high molecular weight polyethylene polymer powder of 50.0-250.0μm.

3. The ultra-high molecular weight polyethylene polymer according to claim 1 or 2, wherein the ultra-high molecular weight polyethylene polymer is a copolymer comprising: at least 98.0 wt% of the moiety derived from ethylene, based on the total weight of the ultra-high molecular weight polyethylene polymer; and Up to 2.0 wt% of the moiety derived from one or more alpha-olefins selected from propylene, 1-butene, 4-methyl-1-pentene, 1-hexene and 1-octene, based on the total weight of the ultra high molecular weight polyethylene polymer.

4. An article prepared from the ultra-high molecular weight polyethylene according to any one of claims 1 to 3, wherein the ultra-high molecular weight polyethylene has the following properties: Powder bulk density of at least 200 kg / m3 as measured by ASTM D1895 / A-1996, reapproved 2010-e1 3 ; An intrinsic viscosity IV of at least 10.0 dl / g as measured by ASTM D4020; A degree of crystallinity Xc greater than 70% as determined by differential scanning calorimetry (DSC); and When the stretching temperature T m –30℃ to T m When stretched between two stretching steps, a sample prepared from the ultra-high molecular weight polyethylene can be stretched at a total stretch ratio of at least 50.0 in the absence of a solvent, wherein T m is the melting temperature of the ultra high molecular weight polyethylene polymer.

5. The article according to claim 4, wherein the article is a stretched article, characterized in that the breaking strength of the stretched article is related to the total stretching ratio DR for preparing the stretched article by the following formula (I): BT>α*ln(DR)–β(Formula I) The total stretch ratio DR is at least 50.0, the breaking strength BT is expressed in N / tex, 0.835≤α≤0.881, 1.787≤β≤1.887, and the ratio α / β is 0.

476.

6. A method for preparing the stretched product of claim 5, comprising the steps of: Compacting ultra-high molecular weight polyethylene polymer powder into a film sample having a length of L1; and Rolling and / or calendering the film sample into a rolled film sample with a length of L2, and a stretching ratio of L2 / L1≥2; and At the stretching temperature T m –30℃ and T m The rolled film sample is stretched to form a stretched product with a length of L3, wherein T m is the melting temperature of the ultra high molecular weight polyethylene polymer, and wherein the rolled film sample is stretched with a stretch ratio represented by L3 / L2 so that the total stretch ratio L3 / L1≥50.

7. The method according to claim 6, wherein: The compaction temperature is T m –30℃ to T m and / or at a pressure >100 bar and <300 bar; and / or The rolling is performed at a temperature of T m –30℃ to T m between implementation; The temperature during rolling is lower than the temperature during compacting.

8. The method according to claim 7, wherein: The compaction temperature is T m –15℃ to T m and / or at a pressure of >150 bar and <250 bar; and / or The rolling is performed at a temperature of T m –15℃ to T m between implementation; The temperature during rolling is lower than the temperature during compacting.

9. A catalyst composition for preparing an ultra-high molecular weight polyethylene polymer according to any one of claims 1 to 3, comprising: a. By general formula (I) L n MX (k-n) A transition metal complex represented by L represents an organic ligand, wherein the organic ligand L is selected from phenoxyimine, phenoxyamine and phenoxyether, M represents a transition metal, wherein the transition metal M is a metal selected from Group IV of the Mendeleev Periodic Table of Elements, X represents a substituent selected from the group consisting of fluorine, chlorine, bromine or iodine, an alkyl group having 1 to 20 carbon atoms, an aralkyl group having 1 to 20 carbon atoms, a dialkylamino group having 1 to 20 carbon atoms or an alkoxy group having 1 to 20 carbon atoms, k represents a positive integer and is the valence of the transition metal 'M', n is an integer defined by 1≤n≤k; and b. a particulate catalyst support comprising particles having a volume median particle size of 0.3-200.0 μm, wherein the transition metal complex is carried on the particulate catalyst support; The particulate catalyst carrier comprises a particulate organic aluminum selected from methylaluminoxane MAO, isobutylaluminoxane, methylisobutylaluminoxane, and ethylisobutylaluminoxane.

10. The catalyst composition according to claim 9, wherein the particulate organoaluminum is methylaluminoxane MAO.

11. The catalyst composition according to any one of claims 9 to 10, wherein the transition metal M is titanium.

12. The catalyst composition according to claim 11, wherein the catalyst composition comprises diphenoxyimide titanium dichloride supported on particulate methylaluminoxane (MAO) particles having a volume median particle size of 0.3 to 200.0 μm.

13. The catalyst composition according to any one of claims 9-10, wherein the catalyst composition further comprises a scavenger additive selected from the group consisting of an organolithium compound, an organomagnesium compound, an organoaluminum compound, an organozinc compound, and a mixture thereof.

14. A process for preparing an ultra high molecular weight polyethylene polymer as claimed in any one of claims 1 to 3, comprising the step of polymerizing ethylene and optionally one or more α-olefins in the presence of a catalyst composition as claimed in any one of claims 9 to 13 and optionally in the presence of hydrogen.

15. The method of claim 14, wherein the catalyst composition comprises diphenoxyimide titanium dichloride supported on particulate methylaluminoxane (MAO) particles having a volume median particle size of 0.3 to 200.0 μm.

Citation Information

Patent Citations

  • Methods and systems for synthesis of an ultra high molecular weight polymer

    US20120095168A1

  • Crop lifter with releasable tips

    US20130118140A1

  • Solid MAO composition containing al2o3 and method for producing same

    US20180355077A1

  • Solid polymethylaluminoxane composition and method for manufacturing same

    US8404880B2

  • Method for manufacturing a small particle diameter product of solid polymethylaluminoxane composition

    US9340630B2